Attenuated release of biologically active luteinizing hormone in healthy aging men. - Urban, R J (1988)
To examine the biological quality and physiologically pulsatile mode of endogenous luteinizing hormone release in active, healthy aging men, we used the rat interstitial-cell testosterone in vitro bioassay to probe LH bioactivity in response to (a) endogenous gonadotropin-releasing hormone (GnRH) action (basal pulsatile bioactive LH secretion); (b) exogenous GnRH stimulation (10 micrograms IV pulses); and (c) inhibition of endogenous estrogen negative feedback (treatment with a nonsteroidal antiestrogen, tamoxifen). Basally, some healthy older men exhibited evidence of neuroendocrine dysfunction, reflected by irregular bursts of bioactive LH release followed by transiently low plasma bio:immuno (B:I) LH ratios. However, mean basal plasma bioactive LH concentrations, B:I ratios, and spontaneous LH pulse properties (peak frequency, amplitude, duration, and enhanced B:I ratios within LH peaks) were not altered in older men. On the other hand, augmentation of bioactive LH secretion and enhancement of plasma B:I ratios by pulsed injections of exogenous GnRH were either significantly reduced or absent in older men. In addition, although tamoxifen increased bioactive LH pulse frequency in both age groups and facilitated exogenous GnRH action in some subjects, older men increased their 12-h mean bioactive LH concentrations, B:I ratios, and bioactive LH peak amplitudes to a significantly lesser degree than young men. In summary, young and older healthy men exhibit similar mean basal plasma bioactive LH concentrations and spontaneous LH pulse properties. However, pituitary bioactive LH reserve is markedly attenuated in older men challenged with either exogenous GnRH or antiestrogen. Accordingly, we conclude that healthy aging men manifest an impaired secretory reserve for biologically active LH release.